PENGARUH WORD OF MOUTH DAN SERVICESCAPE TERHADAP KEPUTUSAN PEMBELIAN - Khalid K Moenardy; Fajar Shavira Cahya Winarni (Universitas Nusa Cendana, 2022)
This study aims to determine the effect of Word Of Mouth and Servicescape on purchasing decisions at dr. Maharani Kupang Skin Care. The independent variables in this study are Word Of Mouth and Servicescape, while the dependent variable is Purchasing Decisions. The number of samples in this study were 80 respondents, namely all active customers of dr. Maharani Skin Care in Kupang. Samples were obtained by using accidental sampling technique. The data analysis technique is Descriptive Quantitative, Multiple Linear Regression Analysis and hypothesis testing using the SPSS version 26. The results of the descriptive analysis show that overall the respondents gave a very good perception of Word Of Mouth and servicescape to dr. Maharani Skin Care in Kupang. Both the results of the t test and the F test show that simultaneously and partially Word Of Mouth and Servicescape have a significant influence on Purchasing Decisions. Based on the Adjusted R2 value, it shows the contribution of Word Of Mouth and Servicescape to Purchasing Decisions is 54.7% while 45.3% is influenced by other variables outside the focus of this study. Other variables are Product Quality, Price, Promotion and Service Quality which can be taken into consideration for further researchers in addition to Word Of Mouth and Servicescape. Keywords: Word Of Mouth, Servicescape, Purchasing Decision